Isaac Shelby papers - Shelby, Isaac, 1750-1826.
Transcript of Shelby's account (1823) of the battle of King's Mountain during the Revolution, together with letters and certificates relating to Col. William Campbell; land grant (1795 December 1) signed by Shelby and issued to Jessee Taylor; and commission (1792 August 9) signed by Shelby appointing Priestley Gray as captain in the Kentucky militia.
In part, handwritten transcript.
Army officer and governor of Kentucky.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Campbell, William, -- 1745-1781.; Gray, Priestley; Taylor, Jessee; King's Mountain, Battle of, S.C., 1780.; Land grants -- Kentucky; Kentucky -- Militia; Kentucky -- Politics and government -- 1792-1865.; South Carolina -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Campaigns; Army officers; Governors -- Kentucky